Lifetime and perceived stress, social support, loneliness, and health in autistic adults - Moseley, Rachel L; Turner-Cobb, Julie M; Spahr, Chandler M; Shields, Grant S; Slavich, George M (Health psychology, 2021)
Although the health consequences of life stress exposure in the general population are well known, how different stressors occurring over the lifetime cause morbidity and mortality in autism is unclear, as are the factors that moderate and mediate these associations. The few studies that have compared autistic and nonautistic individuals have used instruments that yield few stress exposure indices and assess stressors occurring over short time periods. To address these issues, we used the Stress and Adversity Inventory to assess lifetime stressor exposure and perceived stressor severity in 127 autistic and 104 nonautistic adults. Moderated mediation analysis examined associations between stressor exposure and physical and mental ill-health with respect to the hypothesized mediating role of stressor perception, and moderation effects of loneliness and social support. Autistic adults experienced more lifetime stressors and generally perceived stressors as being more severe. Greater perceived stressor severity was related to poorer physical and mental health and to greater loneliness and lower social support for both groups. An additional post hoc analysis of the association between diagnostic status and mental ill-health revealed that loneliness mediated the relation between being autistic and having poorer mental health. Autistic individuals experienced more lifetime stressors, and their impact on physical and mental health was mediated by perceived stressor severity. Moreover, loneliness and low social support were associated with greater negative impact of lifetime stress exposure on mental health. Interventions that reduce cognitive-perceptual stress appraisals, and that target loneliness and social support, may help reduce risk for stress-related disease in autistic individuals. (PsycInfo Database Record (c) 2021 APA, all rights reserved).